The Short Run Capability Improvement Efforts Through Varied Learning Approaches (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2017)
The purpose of this research was done to upgrade the learning approach through the short run variable on the students grade 3 son SD N Krebet 3 Masaran Sragen 2015/2016 school year. This research is Class action, research was conducted with two-cycle and do the analysis it can be concluded that increased learning outcomes atltetik number of short run through the learning variable approach is characterized by an increase in the value of the average student. The average value of the students on the initial conditions of 60.56 with ketuntasan percentage of 6.67%. The condition has increased the value of the average students in cycle I, i.e. of 62.20 and ketuntasan percentage of 10.00%. However, the increase has still not reached the targets set earlier. Then after continuing to cycle II the average value of the short run capability of the students again experienced an increase of ketuntasan percentage of 74.70 with 80.00%. This indicates that the target set previously already accomplished so research stopped in cycle II. The process of learning the number of short run Athletics through learning approach markedly dynamic and fun takes place and the results of observation of the teacher when learning is also increasing in every meeting.